McCARD Criticality Benchmark Analyses with Various Evaluated Nuclear Data Libraries - Ho Jin Park; Mohammad Alosaimi; Seong-Ah Yang; Heejeong Jeong; Sung Hoon Choi (Energies, 2022)
International Criticality Safety Benchmark Evaluation Project (ICSBEP) criticality analyses were conducted using the McCARD Monte Carlo code for 85 selected benchmark problems with 7 evaluated nuclear data libraries (ENDLs): ENDF/B-VII.1, ENDF/B-VIII.0, JENDL-4.0, JENDL-5.0, JEFF-3.3, TENDL-2021, and CENDL-3.2. Regarding the analyses, it was confirmed that the keff results are sensitive to the ENDL. It is noted that the new-version ENDLs show better performance in the fast benchmark cases, while on the other hand, there are no significant differences in keff among the different ENDLs in the thermal benchmark cases. The sensitivity of the keff results depending on the ENDL may impact nuclear core design parameters such as the shutdown margin, critical boron concentration, and power defects. This study and keff results will be a good reference in the development of new types of nuclear cores or new design codes.